Developing the future: An interactive web image based (IWIB) virtual tour of UiTM Pahang / Anis Hasliza Abu Hashim ...[et al.] - Abu Hashim, Anis Hasliza; Hasnan, Mazliana; Ibrahim, Norfiza; Abd Aziz, Maslina; Eelco, de Vries (2007)
A virtual tour (or virtual reality tour) is virtual reality simulation of an actually existing location, usually comprising 2D panoramic images, image- based models of the real location, interactive or still images as well as other multimedia elements such as audio and text. Virtual tour is an immersive technology that places the viewers inside the image, enabling them to significantly enhance situational awareness and providing the highest level of functionality for viewing, capturing and analysing visual data. An interactive web image-based (IWIB) virtual tour of UiTM Pahang provides a tour with free navigation and immersive experience through the WWW By putting the tour on the web, viewers could access to it from every where at any time. This paper describes the prototype developed for IWIB virtual tour of UiTM Pahang.